Novel technique for pediatric ostial cardioplegia delivery. (June 2015) - Mishra, Amit; Hinduja, Manish; Solanki, Atul
Antegrade ostial cardioplegia is an important mode of cardioplegia administration in pediatric patients. We present our innovative, simple, and cost-effective method of pediatric ostial cardioplegia delivery.